HLA Diversity in Saudi Population: High Frequency of Homozygous HLA Alleles and Haplotypes - Chentoufi, Aziz Alami; Uyar, F. Aytül; Chentoufi, Hiba A.; Alzahrani, Khalid; Paz, Maria; Bahnassy, Ahmed; Elyamany, Ghaleb; Elghazaly, Assem (Frontiers in Genetics, 2022)
Human Leukocyte Antigens (HLA) diversity has tremendous impact in shaping the transplantation practices, transfusion associated graft versus host disease prevention strategies and host-pathogen interactions. Here we conducted a retrospective study of HLA class I and class II homozygosity at allelic and haplotype levels in unrelated individuals genotyped from 2012-2016 in a tertiary hospital at the capital of Saudi Arabia. Among 5000 individuals, 2773 individuals meet inclusion criteria and retrospectively analyzed for HLA-A, -B, -C –DRB1 and -DQB1 homozygosity at allelic and haplotype levels. HLA molecular typing was performed using a commercial reverse Sequence-Specific oligonucleotides (rSSO) kit. We were able to identify 15 HLA-A, 20 HLA-B, 11 HLA-C, 13 HLA-DRB1 and 5 HLA-DQB1 homozygous alleles demonstrating a very low genetic diversity in Saudi population. The highest homozygosity in HLA class I was found in locus C followed by A and B (20.3%>16.1% > 15.5%; p<0.001) where the most homozygote alleles were A*02 (9.2%), B*51 and B*50 (5.7% and 3.7%), and C*07, C*06 and C*15 (7.2%, 5.48%, 3.3%) and in HLA class II the highest homozygosity was found in locus DQB1 compared to DRB1 (31.71% > 19.2%; p<0.001) with the most common Homozygote alleles were DRB1*07 and DRB1*04 (5.33% and 4.2%) and DQB1*02, DQB1*06 and DQB1*03 (13.55%, 7.92%, 7.64%). The frequency of finding an individual with one homozygote allele was (24.6%), two homozygote alleles (13.5%), three homozygote alleles (4.7%), 4 homozygote alleles (3.4%) and 5 alleles was (4.8%). The most frequent homozygote haplotype A*23~C*06~B*50~DRB1*07~DQB1*02 and A*02~C*06~B*50~DRB1*07~DQB1*02. This study shows low diversity of both class I and II alleles and haplotypes in Saudi population which would have a significant impact in shaping the transplantation practices, transfusion associated graft versus host disease prevention strategies and host-pathogen interactions.